"Price Levels and Economic Growth: Making Sense of Revisions to Data on Real Incomes": A Comment. (13th October 2013) - Inklaar, Robert
Abstract : In his recent paper, Ravallion (2013) proposes a new method to predict changes in purchasing power parities (PPPs), arguing that a model that includes economic growth and exchange rate movements is superior to the standard approach of using inflation differences. In this comment, I argue that his test is wrong and I show that with a correct specification of the test, there is no robust and stable relationship between changes in PPPs and economic growth while the usefulness of the standard approach is confirmed. I also suggest an approach that could be more helpful to understand changes in PPPs.